The last time I saw Paris - Brooks, Richard, 1912-; Taylor, Elizabeth, 1932-; Johnson, Van, 1916-; Reed, Donna, 1921-1986.; Pidgeon, Walter, 1897-; Gb̀or, Eva, 1921- (Canada Media, Movies and More, 2005)
A writer looks back on an old romance in Paris with a lonely, rich American young woman.
Based on Babylon revisited by F. Scott Fitzgerald.
Director, Richard Brooks ; producer, Jack Cummings ; screenplay, Julius J. Epstein, Philip G. Epstein, Richard Brooks ; director of photography, Joseph Ruttenberg ; music, Conrad Salinger.
Elizabeth Taylor, Van Johnson, Walter Pidgeon, Donna Reed, Eva Gabor, Kurt Kasznar.
DVD.
Keywords: Feature films